(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Natsir SM. 2022. The distribution of benthic foraminifera in coral reefs ecosystem of East Penjaliran Island, Seribu Islands, Indonesia. Biodiversitas 23: 3073-3080. East Penjaliran Island is located in the core zone of Seribu Islands Marine National Park and is included in the protected green area. The research shows the close relationship between benthic foraminifera and coral reef. Certain foraminifera has the same environmental requirement to live with coral reefs. Therefore, the study of foraminiferal assemblages is also very important to shed light on the environmental conditions for the growth of coral reefs through calculating the Foraminifera in Reef Assessment and Monitoring Index (FORAM Index/FI). Sampling was conducted in December 2016 around the coral reef ecosystems of East Penjaliran Island, Seribu Islands. A total of 37 species of benthic foraminifera were collected from the island with a diverse abundance. Based on the FI gained values on average of 3.18. It indicates that East Penjaliran Island is classified as an environmental change for coral reefs’ growth. The condition was feasible for the growth of coral reefs, but it tends to be an unfavorable environment for their recovery. The benthic foraminifera assemblages can be classified into three major groups based on the Shannon diversity index and FI (i.e., Group A, Group B, and Group C) with their specific characteristics. Group A was characterized by coarse sand sediment and dwelled dominantly by opportunistic foraminifers such as Elphidium advenum, Elphidium crispum, and Flintina bradyana. Groups B and C have very fine sand sediment, but they dwelled by foraminiferal assemblages in different compositions. Group B was dominated by E. crispum and followed by several species of Peneroplis, but Group C dwelled abundantly by E. advenum, E. crispum, Elphidium depressulum and followed by symbiont-bearing foraminifera such as Peneroplis planatus.